EMOTIONAL DEVELOPMENT STRATEGY IN ACHIEVEMENT OF STUDENT LEARNING RESULTS 4th GRADE IN MIT AR-ROIHAN LAWANG - Devi Wahyu Ertanti; Halimatus Sakdiyah (VICRATINA, 2017)
Abstract This study aims to determine the state of emotional intelligence of students in 4th grade, emotional intelligence development strategy of 4th grade  students, as well as supporting and inhibiting factors in developing emotional intelligence to academic learning outcomes of 4th grade students at MIT Ar-Roihan Lawang. The research approach used in this research is qualitative approach because it is in accordance with the characteristics of qualitative research. The strategy used in the qualitative research discussed is the field research strategy. In this study, researchers in the field become the main requirement, researchers collect research results in the natural setting, where researchers act as key instruments. In addition, researchers also act as planners and implementers of class actions that are directly involved, collecting and analyzing the results of research and eventually become reporting research results. The results showed that high emotional intelligence is not a determinant of students will get high academic learning results as well. Each learner has different potential with other learners.Keywords: Development Strategy, Emotional Intelligence, Academic Learning Outcomes.